Electrochemical Sensor and Biosensor Detection of Ethanol in Beverage Samples: - Irkham, Irkham; Zalfadilah, Faizal Nur; Zein, Muhammad Ihda Hamlu Liwaissunati; Khaerani, Wulan; Zakiyyah, Salma Nur; Hartati, Yeni Wahyuni (Journal of Advanced Technology and Multidiscipline, 2025)
Ethanol detection is critical in the beverage industry, where it is essential to monitor alcohol concentrations for quality control and compliance with regulatory standards. Traditional analytical methods, such as gas chromatography and distillation, offer accuracy but are often labor-intensive, time-consuming, and require sophisticated equipment. In contrast, electrochemical sensors and biosensors have emerged as promising alternatives due to their rapid response, portability, cost-effectiveness, and potential for real-time monitoring. Electrochemical sensors, particularly those enhanced with metal nanoparticles like platinum, palladium, or gold, have shown significant improvements in sensitivity, selectivity, and response time. These sensors offer the advantage of miniaturization, making them ideal for on-site analysis, although issues such as electrode stability, susceptibility to interference, and long-term reliability remain. On the other hand, biosensors, which leverage biorecognition elements like alcohol dehydrogenase (ADH) or alcohol oxidase, provide high specificity for ethanol, reducing interference from other compounds commonly found in beverage samples. Recent advancements in biosensor technology have focused on improving sensor stability, enzyme immobilization techniques, and reducing production costs. While biosensors offer high selectivity and sensitivity, they may still face challenges related to enzyme denaturation and environmental factors such as temperature and pH fluctuations. Both electrochemical sensors and biosensors are continuously evolving, with recent developments including the use of nanomaterials and novel biorecognition elements to enhance performance. This review will explore recent advances in electrochemical sensors and biosensors for ethanol detection in beverage samples, highlighting their potential, challenges, and future directions in this field.